Development of Matryoshka Animal Media of Thematic Learning for Sixth Grade of Elementary School - Anggraeni, Jurnalita Rose; Restian, Arina; Regina, Belinda Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
The research of matryoshka animal media development is established based on the problem that exists which is the students' characteristic of inability to focus on and the teacher who got difficulty in giving understanding upon the teaching material toward the students. Therefore, the researchers create a concrete tool for the learning targets. The aims of this research are: (1) to know and describe the development of the matryoshka animal media in thematic learning in grade IV theme 6 sub-theme 2 in SDN Ketawanggede Malang; (2) to know and describe the application of matryoshka animal media in thematic learning in grade VI theme 6 sub-theme 2 in SDN Ketawanggede Malang. This research used ADDIE developmental model. This developmental ADDIE model has 5 stages which are analysis, design, development, implementation, and evaluation. The data analysis technique used in this research is quantitative and qualitative to know the applicable product that has been developed. This research was done in grade IV of SDN Ketawanggede. The result from this developmental research of matryoshka animal media on thematic learning in grade IV theme 6 sub-theme 2 based on the scoring percentage which is (1) the percentage of material validation is 85% within a valid category, and master of media is 88% within a valid category, and right to be used. While the percentage of teachers' responses is 100% and students' response from 25 students shows 96% and pass the criterion. Based on the percentage matryoshka animal media is passed and right to be implemented.